Authenticating honey origin from Natural Park of Montesinho: innovative electrochemical genosensor devices assembled in paper-based transducers - Pereira, Eduarda (2023)
The Natural Park of Montesinho (NPM) has a diverse ecosystem that is home to countless species of trees and plants characteristic of this area, including Castanea sativa. The honey produced in this region is highly appreciated for its taste and nutritional value, but it also has a wide range of health benefits. The geographical origin of the honey is a very important aspect in assessing the quality and authentication of the final product. Currently, several approaches are being explored to determinethese parameters, among which deoxyribonucleic acid (DNA)-based methods stand out.